2022
DOI: 10.1590/acb370205
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of Blaps rynchopetera extract

Abstract: Purpose: To explore the potential immunomodulatory effects of total extract and different polar parts from Blaps rynchopetera Fairmaire. Methods: Phagocytic activity was evaluated by neutral red assay, and the effect of the immune function was investigated by normal and immunocompromised mice models. Results: In vitro , total extract, as well as chloroform, ethyl acetate, n-butanol and water fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…It may not be universally applicable to all cancer patients due to the complex nature of the disease. As a result, polysaccharide therapy is often employed in combination with other treatment methods to achieve the most effective therapeutic outcome [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may not be universally applicable to all cancer patients due to the complex nature of the disease. As a result, polysaccharide therapy is often employed in combination with other treatment methods to achieve the most effective therapeutic outcome [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanolic extractions from this species have rendered five rynchopeterines (A-E), in addition to other phenolic compounds associated with antioxidant activity, such as protocatechuic acid, 3,4-dihydroxyphenylacetic acid, 3,4-dihydroxybenzaldehyde, and 3,4-dihydroxyphenylacetaldehyde, among others (37). Recently, some reports have shown that the extracts obtained from B. rynchopetera have an immunomodulating effect; therefore, it has attracted greater interest in the fields of medicine and nutrition (39).…”
Section: Phenolic Compounds In Potentially Edible Insectsmentioning
confidence: 99%
“…In recent years, the chemical composition and medicinal value of B. rhynchopetera have been increasingly researched and explored. Extracts from this beetle have exhibited immunomodulatory [5] , treatment for vaginal inflammation [6] , antibacterial [7] . Moreover, the defensive secretion of B. rhynchopetera may be an important source of tumor drug development and biomedicine [8] .…”
Section: Introductionmentioning
confidence: 99%